STEP – ein Paradigmenwechsel in der europäischen Wirtschaftspolitik? - Dirk H. Kranen; Stephan Freitag (Wirtschaftsdienst, 2024)
The new Strategic Technologies for Europe Platform (STEP) is intended to channel investments into economic sectors that are considered strategically important and thus strengthen European competitiveness. To this end, STEP will make it possible for the first time to support large companies on a broad scale with EU structural funds. The European Commission regards STEP as a precursor to an instrument for a comprehensive EU industrial policy. Against this background, the emerging paradigm shift towards a more dirigiste European economic policy is examined.
Keywords: E60; H50; R10; 330